Penguatan Karakter Anak Usia Dini Melalui Pengenalan Rukun Iman dan Islam di MDTA Al-Jauharotunnaqqiyyah Link. Kedung Baya - Fahrijal Taufik Hidayat; Faujiyah Faujiyah; Fathiyah Fathiyah; Rosihah Rosihah; Tiara Nofiana; Slamet Gunadi; Yolla Sukma Handayani; Asih Setyo Rini (Jurnal Budi Pekerti Agama Islam, 2024)
This research explores the effectiveness of religious singing methods in teaching the Pillars of Faith and the Pillars of Islam to young children at MDTA Al-Jauharotunnaqqiyyah, Kedung Baya. Character education at an early age is very important to form a strong personality, and instilling Islamic values from an early age plays a significant role in this process. This research method uses a qualitative approach with a case study design, involving direct observation and interviews with students to collect data about their understanding of religious teachings and their impact on behavior and character. The research results show that the religious singing method is effective in increasing children's understanding of the Pillars of Faith and the Pillars of Islam, as well as increasing their involvement in learning. Positive responses from parents and teachers confirm that this method makes religious teachings more interesting and applicable. However, challenges such as differences in children's levels of understanding, limited resources, and integration with the curriculum need to be overcome to maximize the effectiveness of this method. This research concludes that the religious singing method is an innovative approach that can be widely applied to support character education, with continuous evaluation and adjustment as the key to success.